Operational Flexibility of Two-Phase Flow Test Rig for Investigating the Dynamic Instabilities in Tube Boiling Systems - Temraz, Ayman; Alobaid, Falah; Lanz, Thomas; Elweteedy, Ahmed; Epple, Bernd (Frontiers in Energy Research, 2020)
The safe operation of a two-phase heat exchanger can be performed by determining the instability threshold values of power plant parameters. Thus, the power plant parameters must be designed outside these thresholds to avoid undesirable instability. The fluctuations in mass flow and system pressure are undesirable processes, resulting in system failure. In diverse heat transfer distribution, that can lead to burn-out of heat exchanger tubes. Therefore, the maintaining of flow stability in a power plant is of particular relevance. The researchers and engineers can predict the threshold of flow instability with dynamic models validated with experimental records. The phenomenon of dynamic flow instabilities in two-phase flows is an important issue that has high relevance for many industries. The awareness about the triggers and the effects of fluid dynamic instabilities is of great importance in the design and operation of steam generators, refrigeration systems, thermosiphons or boiling water reactors. These instabilities manifest themselves in variations of mass flow, pressure, and fluid properties. In this work, the dynamic instabilities involved in evaporation processes were briefly discussed with simple models to understand the mechanism of its different types. Additionally, it is presented the design and construction of a two-phase flow test rig using the similarity and the scaling criteria. A heat recovery steam generator (HRSG) designed by Doosan Heavy Industries and Construction is scaled down to 4 m x 4 m x 2 m. The combination of the flow diagram and the thermohydraulic design is represented in three-dimension model of the test rig using the Siemens NX 10.0 software. The flexibility of operation was taken into account in the design of this test rig.